Effective calibration of an endoscope to an optical tracking system for medical augmented reality. Issue 1 (1st January 2017) - Lee, Seongpung; Lee, Hyunki; Choi, Hyunseok; Jeon, Sangseo; Hong, Jaesung
Abstract: Background : We investigated the methods of calibrating an endoscope to an optical tracking system (OTS) for high accuracy augmented reality (AR)-based surgical navigation. We compared the possible calibration methods, and suggested the best method in terms of accuracy and speed in a medical environment. Material and methods : A calibration board with an attached OTS marker was used to acquire the pose data of the endoscope for the calibration. The transformation matrix from the endoscope to the OTS marker was calculated using the data. The calibration was performed by moving either the board or the endoscope in various placements. The re-projection error was utilized for evaluating the matrix. Results : From the statistical analysis, the method of moving the board was significantly more accurate than the method of moving the endoscope ( p < 0.05). This difference resulted mainly from the uneven error distribution in the OTS measurement range and also the hand tremor in holding the endoscope. Conclusions : To increase the accuracy of AR, camera-to-OTS calibration should be performed by moving the board, and the board and the endoscope should be as close as possible to the OTS. This finding can contribute to improving the visualization accuracy in AR-based surgical navigation.